Application of the Optimized Decoupling Methodology for the Construction of a Skeletal Primary Reference Fuel Mechanism Focusing on Engine-Relevant Conditions - Chang, Yachao; Jia, Ming; Li, Yaopeng; Xie, Maozhao (Frontiers in Mechanical Engineering, 2015)
For the multi-dimensional simulation of the engines with advanced compression-ignition combustion strategies, a practical and robust chemical kinetic mechanism is highly demanded. Decoupling methodology is effective for the construction of skeletal mechanisms for long-chain alkanes. To improve the performance of the decoupling methodology, further improvements are introduced based on recent theoretical and experimental works. The improvements include: (1) updating the H2/O2 sub-mechanism; (2) refining the rate constants in the HCO/CH3/CH2O sub-mechanism; (3) building a new reduced C2 sub-mechanism; and (4) improving the large-molecule sub-mechanism. With the improved decoupling methodology, a skeletal primary reference fuel (PRF) mechanism is developed. The mechanism is validated against the experimental data in shock tubes, jet-stirred reactors, premixed and counterflow flames for various PRF fuels covering the temperature range of 500–1450 K, the pressure range of 1–55 atm, and the equivalence ratio range of 0.25¬–1.0. Finally, the skeletal mechanism is coupled with a multi-dimensional computational fluid dynamics model to simulate the combustion and emission characteristics of homogeneous charge compression ignition (HCCI) engines fueled with iso-octane and PRF. Overall, the agreements between the experiment and prediction are satisfactory.